The emperor of law : the emergence of Roman Imperial adjudication - Tuori, Kaius (Oxford studies in Roman society and law, 2016)
'The Emperor of Law' explores how the Roman emperor came to assume the mantle of supreme legal authority in the Empire. It offers a fundamental reinterpretation of the advent of imperial supremacy in law based on an analysis of the gradual expansion and elaboration of the emperor's adjudication and jurisdiction through historical narratives